Administrative restructuring and urban development in China: Effects of urban administrative level upgrading. (May 2020) - Wang, Jiejing; Yeh, Anthony GO
This study focuses on state-led urbanisation in the Chinese context by examining the effects of urban administrative level upgrading on urbanisation and urban development. We argue that urban administrative level upgrading is an important policy instrument in China that empowers cities to play a leading role in driving national and regional economic development. However, there is a lack of systematic empirical investigation to determine whether the objectives of urban administrative level upgrading have been achieved. Using a quasi-experimental method that combines propensity score matching with the difference-in-difference approach, we thoroughly examine the effects of county- to prefecture-level city upgrading and county to county-level city upgrading on the development performance of cities. The results confirm that county- to prefecture-level city upgrading can positively lead to a significant increase in urban population growth and fiscal revenue in a few years after upgrading, although this may not necessarily lead to rapid industrialisation. However, the same is not true for county to county-level city upgrading. This difference may be because counties and county-level cities are at the same administrative level, whilst prefecture-level cities are at a higher administrative level compared with county-level cities and counties. The results indicate that China's administrative division system, although restructured, retains hierarchical and level-based structure in the post-reform period. We highlight the continuing strategic role of the Chinese state by establishing new scales and arenas and adjusting administrative structures to promote urban development.